HUBUNGAN PERAN PENGAWAS MINUM OBAT OLEH KELUARGA TERHADAP PENGETAHUAN KELUARGA PENTINGN PENGOBATAN TBC DI WILAYAH KERJA PUSKESMAS PERAWANG KEC. TUALANG KAB. SIAK 2019 - Putri Wulandini; Aulia Sintiawati; Roni Saputra (Jurnal Keperawatan Abdurrab, 2020)
The family can be used as a Drug Supervisor (PMO), because it is known, trusted and approved, both by health workers and sufferers, in addition it must be respected, respected and live close to sufferers and willing to help sufferers voluntarily. The purpose of this study was to determine the relationship of PMO by families to knowledge about the importance of TB treatment. This research uses quantitative research and correlation design with cross sectional approach. This research was conducted in the Perawang Health Center Work Area Kec. Kab. Kab. Siak The population in the study were all tuberculosis patients, amounting to 150 people. The sample in this study was taken with the Total Sampling technique. Data collection is done by distributing questionnaires containing 30 statements and then processed with steps of editing, coding, data entry, and cleaning, then analyzed by univariate and bivariate. The results showed that the relationship between the role of the PMO by the family against knowledge, it is hoped that officers will further motivate families with TB to make repentance. Keywords: Role of PMO, Family, Knowledge, TB